Use of oral anticoagulants after ischaemic stroke in patients with atrial fibrillation and cancer. (29th May 2020) - Atterman, A.; Asplund, K.; Friberg, L.; Engdahl, J.
Abstract: Background and objectives: The use of oral anticoagulants (OACs) amongst patients with atrial fibrillation (AF) has increased in the last decade. We aimed to describe temporal trends in the utilization of OACs for secondary prevention after ischaemic stroke amongst patients with AF and active cancer. Methods: This is a cross‐sectional and cohort study of patients with active cancer ( n = 1518) and without cancer ( n = 50 953) in the Swedish national register Riksstroke, including all patients with ischaemic stroke between 1 July 2005 and 30 December 2017, discharged with AF. Prescription and dispensation before and after the introduction of nonvitamin K OACs (NOACs) in late 2011 were compared. We used logistic and Cox regression to analyse associations with OAC use, adjusting for hospital clustering and the competing risk of death. Results: The proportion of cancer patients with AF prescribed OACs at discharge after ischaemic stroke increased by 40.2% after 2011, compared with 69.3% in noncancer patients during the same period. Stroke and bleeding risk scores remained similar between patients with and without cancer. OAC dispensation during the following year did not increase as much in cancer patients (43.8% to 64.5%) as that in noncancer patients (46.0% to 74.9%), and the median time to OAC dispensation or censoring was significantly longer in cancer patients (94 vs. 30 days). Conclusion: OAC treatment in poststroke patients with AF and active cancer has increased after the introduction of NOACs. However, the growing treatment gap in these patients compared to that in noncancer patients raises the possibility of underutilization. Abstract :